Study of wheat (Triticum aestivum L.) breeding material potential for (Triticum aestivum L.)androgenesis - N. V. Petrash; T. N. Kapko; V. V. Sovetov (Вавиловский журнал генетики и селекции)
Doubled haploid technology is a valuable biotechnological approach in plant breeding that enables one to quickly create new varieties through the single-stage production of homozygous lines. The aim of this study was to assess the indicators of in vitro androgenesis in the anther culture of the initial breeding material of varieties and combinations of F1 and F2 and to identify promising accessions with good responsiveness. For that purpose, the plant material that proved promising for the breeding programs of Siberian Research Institute of Plant Production and Breeding (SibRIPP&B) was used. Ten cultivars of common wheat and the F1 and F2 hybrids of nine combinations were evaluated for the main parameters of in vitro androgenesis such as the number of new formations, albino, green and all regenerated plants. Induction of androgenesis in vitro was carried out in anther culture in growth medium Chu (N6) containing 1 mg/l of growth regulator 2,4-D. The studied samples showed different responses to induction. The maximum level of new formations was found in F2 hybrids Novosibirskaya 15 × Lutescens ShT-335. The largest number of green plants was found in F1 Novosibirskaya 15 × Lutescens ShT-335. According to the results of variance analysis, a significant ( p < 0.01) influence of genotype on the studied traits was established. Varieties with good responsiveness to anther culture (Novosibirskaya 15) and lack of responsiveness to in vitro androgenesis (Novosibirskaya 31) were identified. Novosibirskaya 16 was characterized by a low regeneration capacity of new formations. A significant heterotic effect was revealed considering the number of new formations per 100 anthers among the hybrids of such combinations as Novosibirskaya 15 × Lutescens ShT-335, Novosibirskaya 15 × Lutescens 111/09, and Zagora Novosibirskaya × Obskaya 2. Novosibirskaya 15 was recommended for inclusion in crossings as a parental form that provides high hybrid responsiveness during in vitro androgenesis. The use of doubled haploid technology made it possible to quickly create DH-lines based on the breeding material.